2013
DOI: 10.1017/s146114571300093x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling olanzapine-induced weight gain in rats

Abstract: The second-generation antipsychotic drug olanzapine has become a widely prescribed drug in the treatment of schizophrenia and bipolar disorder. Unfortunately, its therapeutic benefits are partly outweighed by significant weight gain and other metabolic side effects, which increase the risk for diabetes and cardiovascular disease. Because olanzapine remains superior to other antipsychotic drugs that show less weight gain liability, insight into the mechanisms responsible for olanzapine-induced weight gain is cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 115 publications
3
24
0
Order By: Relevance
“…The female rats were used in this study, because the SGAinduced weight gain model has been consistently established and validated in female rats in our and other laboratories [27,[63][64][65], while it could not be consistently modelled in male rodents [66]. Clinically, it is also a common observation that female patients have a much higher risk than males for SGA-induced weight gain and other metabolic side-effects [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…The female rats were used in this study, because the SGAinduced weight gain model has been consistently established and validated in female rats in our and other laboratories [27,[63][64][65], while it could not be consistently modelled in male rodents [66]. Clinically, it is also a common observation that female patients have a much higher risk than males for SGA-induced weight gain and other metabolic side-effects [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of energy expenditure, APDs such as olanzapine reduce locomotor activity in rodent models, which further disrupts the balance between energy intake and consumption and leads to weight gain (van der Zwaal et al, 2014 ). Moreover, these olanzapine-induced decreases in locomotor activity occur at doses that do not affect eating behavior (Weston-Green et al, 2011 ).…”
Section: Apd-induced Effects On Appetite and Energy Consumptionmentioning
confidence: 99%
“…Moreover, these olanzapine-induced decreases in locomotor activity occur at doses that do not affect eating behavior (Weston-Green et al, 2011 ). It has been suggested that APDs' sedative properties play an important role in causing this diminished energy consumption (van der Zwaal et al, 2014 ). Consistent with this, there is significant incidence of somnolence in people treated with many second-generation APDs (Gao et al, 2008 ).…”
Section: Apd-induced Effects On Appetite and Energy Consumptionmentioning
confidence: 99%
“…In rodents, the metabolic effects of APD treatment appear to be more robust in females [See review (Van Der Zwaal et al 2014)]. The preclinical findings in female adolescent rodents are in line with the clinical reports that adolescent patients are susceptible to the metabolic effects of APDs.…”
Section: Metabolic Effects Of Adolescent Apd Administrationsupporting
confidence: 62%